EFFECT OF SOCIO-ECONOMIC VARIABLES OF THE RESPONDENTS ON PRODUCTION TRAITS OF CATTLE (Indian Journal of Animal Production and Management, 2013)
The study was carried out in Churu district of Rajasthan to acquire information on effect of socio- economic variables of respondents on production traits of cattle. It was observed that 52 percent of the respondents belonged to old age group, about one third (30.25%) belonged to illiterate category, 45.75 percent had medium size herd, majority (57.00%) of the respondents had large land holding and 43.75 percent had medium size family. The age at first breeding was lower in young age group but it was non-significant with other age groups. The education level had significant influence on age at first breeding and age at first calving. Young age, high educated, large herd size, large land holding and small family size farmers’ animals had less inter calving period than other groups but it was non-significant. Large herd size had significant influence on service period. Age, education level, herd size, land holding and family size had non significant effect on lactation length. The herd size had significant effect on dry period of cows.
Keywords: Cattle; effect; respondents; production traits and selected traits